THE LEGEND OF CASSAVA AS A STRATEGY FOR MEANINGFUL READING: AMAZONIAN CULTURE, TEXTUAL GENRE, AND TRADITION IN EARLY CHILDHOOD EDUCATION - Soares Martins, Adrielly; de Souza Britto, Aldeyses; da Conceição Dias, Flávia; dos Santos Freitas, Marcos; Marinho Cardoso, Naylana; de Souza de Alfaia, Roger; Sofia Lima Azevedo, Samia; dos Santos Colares, Tatiana; Macedo Ribeiro, Edinelza (Revista Gênero e Interdisciplinaridade, 2025)
This article discusses the use of the cassava legend as a pedagogical strategy for meaningful reading in the early grades of elementary school, relating it to Amazonian culture and the traditional practice of cassava flour production. Its general objective is to analyze how the cassava legend can be (re)signified in early childhood education as a didactic resource to encourage meaningful reading. The research, with a qualitative approach, was carried out through a field experience in the Nova Esperança community, in Parintins-AM, where data were collected through interviews and observations. The research results show that the experience strengthens pedagogical initiatives that can be adapted and replicated in early childhood education. Adaptations with interviews, direct observations, visual records, and field trips become fundamental resources as supports for reading, interpretation, and text production. Proposing the reading of the legend in the classroom and, subsequently, conducting a field trip where children can have contact with nature, contributes to a more realistic interpretation, as it develops and stimulates their understanding of the world reflected in their culture. Thus, imagination, creativity, language, and values ​​such as respect, diversity, and cooperation bring it closer to learning within the family and community context. And this represents meaningful reading.